The Influence of Leadership Style on Employee Performance - Jani, Jani; Suryadinata, Sandi (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims 1) to understand the leadership style applied in the Mega Kemayoran area by PT. Nairindo Servitama, and 2) to assess the positive impact of leadership style on employee performance. The research population includes 120 employees who work in the operational section of PT. Nairindo Servitama in the Mega Kemayoran area. This research involved 30 respondents as samples, with sampling using the incidental sampling method. Data collection was carried out through the use of a questionnaire, and data analysis was carried out using a simple linear regression analysis method. From the research results, it can be concluded that 1) PT. Nairindo Servitama Area Mega Kemayoran applies a democratic leadership style, and 2) there is a positive impact of leadership style on employee performance at PT. Nairindo Servitama Mega Kemayoran area.   Keywords: Leadership style, Performance